Dinamika Eksistensi Agama pada Ruang Publik Era Globalisasi di Indonesia - Syaripulloh; Farkhan Abdurochim Alfarauq; Sultan Tirta Mujtaba (PANALUNGTIK, 2025)
This study examines the dynamics of religion in the public space in Indonesia during the era of globalization. Using a qualitative approach with library research and content analysis, the study applies Peter Beyer’s theory of globalization and religion to analyze the interaction between religious and global forces in Indonesia through four key dimensions: economic, political, cultural, and social systems. The findings reveal that although Indonesia is not a theocratic state, religion continues to play a significant role in both state affairs and the social life of modern Indonesian society. This research highlights how religion adapts and transforms in response to globalization, maintaining its public relevance despite predictions of secularization.